Одрживост и перспективе Северно Македонске млечне индустрије - Sulejmani, Erhan; Iseni, Miranda (Journal of Agricultural Sciences (Belgrade), 2023)
The subject of this review is the dairy industry in the Republic of North Macedonia. This industry can generate many economic and social benefits for society and the economy. The paper provides a description and analysis of the current situation within the dairy industry in our country. The production rates of milk in our country are analyzed, applying a comparative approach to production rates at the global and European levels. In the Republic of North Macedonia, milk production is characterized by many small farms - traditional farmers (75% of the total number) who have low productivity of 1 - 3 cows with low annual milk production of 2- 3 thousand litres per cow. The number of large specialized farms with more than 20 cows (about 3% of the total) with high productivity and annual milk production of about 5 thousand litres per cow is minimal. Only 1% of farms have more than 50 heads. In conclusion, for the sustainable dairy industry, all activities should be undertaken in partnership with the industry (along the value chain), policymakers and a wide range of stakeholders, including consumers.